Introduction to Final Cut Pro X - Linaschke, Joseph (Peachpit Press, 2011)
"This innovative product uses interactive video to give viewers an overview of the features in Final Cut Pro X, which Apple has redesigned from the ground up. Final Cut Pro X should be much more accessible to 'pro-sumer' videographers, many of whom shoot video with their digital SLR cameras. This video is geared to this new audience, taking them through the fundamentals of video editing, as well as how to get going quickly with Final Cut Pro X, which still is an advanced, pro-level application. Experienced instructor Joseph Linaschke presents up to four hours of high-quality HD video, complete with lesson files to practice freshly gained knowledge. The videos include a downloadable booklet that provides supplemental material to enhance the video training."--Resource description page.
Title and author name taken from end credits. - Imprint from resource description page (viewed Feb. 16, 2012)
Keywords: Final cut (Electronic resource); Digital video -- Editing -- Data processing; Vidéo numérique; Montage; Informatique; Digital video; Editing; Data processing